Incidencia del liderazgo escolar en el aprendizaje activo de los estudiantes de la Escuela de Educación Básica “28 de mayo” de la Parroquia Ricaurte, Cantón Urdaneta, Provincia de los Ríos. - Jose Miguel, Bajaña Villalba (2015)
Having examined work of degree the present; I must show that the same one has allowed me to establish the weaknesses and strengths that the educative institution has, where I carried out this investigation; since the scholastic Leadership is an important part in the education; because by means of this, the educative institution will have an organization and a direction in common, of the objectives that are wanted to obtain for the active learning of their students. The subject of the scholastic leadership is of much importance at the present moments; since we previously found in the educative institutions, they were people who thought that the being manager of an institution or to have the high rank but, would benefit to him to be located in a privileged seat of honor but without considering the so great responsibility that they had in its hands, being a leader in the institution; where it stops many people the lucrative part was but important that the well-being of the students and who the same knowledge. This work tries to offer an ample vision but and makes specific, since it is possible to be determined the weaknesses and strengths, that served as base to be able to make an efficient and conscious work but according to their realities and style of life within the educative institution. And this way, my desire is that conscience becomes, back leaves the old practices in the educative institutions; so that they become social and democratic